Extension delivery system before and after the devolution, Calabarzon, Philippines. (2013)
In 1967, the extension delivery system in the Philippines was decentralized from the national government to the provincial units based on Republic Act 5185. However, a radical institutional shift on the extension delivery system was made in 1991 through the devolution of extension workers to the local government units. In 2008, the government proposed the centralization once more of the extension delivery system under the national government for efficiency and effectiveness. This study showed how extension services were delivered before 1991 and 15 years after the devolution of extension workers to the local government units. The points of view of the client and the change agents, involving 170 farmers and 48 extension workers from five Calabarzon provinces with representation from five classes of municipalities were included. The study revealed that change agents regardless of municipality class performed their function well as attested by the farmer respondents.extension methods implemented within the municipality classes did not differ. The devolution empowered farmers by financing the activities in their farm, one-third received full or partial support from the municipal government , and by increasing their level of participation in project management. Extension workers wanted centralization because of the motivation factors available before devolution, like the acknowledgement and recognition of superior institution, free hand over his time, and self fulfillment in helping the target group. Clients and beneficiaries of the extension delivery system after assessing the situation prefer the condition after the devolution due to the following reasons: there were consultation in planning and decision making and programs implemented were more effective in giving solution to problems. Extension delivery system should be placed in the hands of the local government units whose priority is the empowerment of its clients.